2017
DOI: 10.3390/nu9040316
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-I-Converting Enzyme (ACE)-Inhibitory Peptides from Plants

Abstract: Hypertension is an important factor in cardiovascular diseases. Angiotensin-I-converting enzyme (ACE) inhibitors like synthetic drugs are widely used to control hypertension. ACE-inhibitory peptides from food origins could be a good alternative to synthetic drugs. A number of plant-based peptides have been investigated for their potential ACE inhibitor activities by using in vitro and in vivo assays. These plant-based peptides can be obtained by solvent extraction, enzymatic hydrolysis with or without novel fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 122 publications
(277 reference statements)
3
165
0
1
Order By: Relevance
“…In addition, microencapsulation of hydrolysates plus incorporation of masking agents are effective alternatives for attenuation of bitterness in hydrolysates. Daskaya-Dikmen et al (2017) claimed that encapsulation of peptides in hydrolysates is the most favorable technique in order to reduce bitterness. Favaro-Trindade et al (2010) reported that bitter taste decreased when casein hydrolysates were spray-dried and mixed with gelatin and soy protein isolate as carriers.…”
Section: Removing Bitternessmentioning
confidence: 99%
“…In addition, microencapsulation of hydrolysates plus incorporation of masking agents are effective alternatives for attenuation of bitterness in hydrolysates. Daskaya-Dikmen et al (2017) claimed that encapsulation of peptides in hydrolysates is the most favorable technique in order to reduce bitterness. Favaro-Trindade et al (2010) reported that bitter taste decreased when casein hydrolysates were spray-dried and mixed with gelatin and soy protein isolate as carriers.…”
Section: Removing Bitternessmentioning
confidence: 99%
“…As previously reported, ACE-inhibitory activity of peptides is affected by their amino acids content. Potent ACE-inhibitory peptides contain short amino acids sequence between 2-12 residues and crystallographic studies have shown that large peptides may not bind to the active sites of ACE (23 - 25). The type of amino acids could be more relevant than the length of the peptide sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Majority of the previously reported ACE-inhibitory peptides derived from food sources contain pro and aromatic amino acids such as Tyr, Tryp or Phe at their C terminal (4, 16, 24, 28) and/or branched aliphatic amino acids such as Val, Leu, Ile at their N terminal (23). The positively charged amino acids arginine (R) and lysine (K) present at the C-terminal were also found to contribute to the ACE inhibitory potency of peptides (29).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of literatures have reported that the chain length, amino acid composition, amino acid sequence and spatial structure have a great influence on the activity of ACE inhibitory peptide. Long peptides are difficult to bind to the active sites of ACE, so most of the high active ACE inhibitory peptides have a chain length of 2-12 amino acids, the lower the molecular weight (<3kDa), the higher the inhibitory activity [36,60,61]. However, in many cases, the influence of amino acid type and sequence on ACE inhibitory activity of peptide is much greater than that of peptide chain length.…”
Section: Antihypertensive Active Peptidementioning
confidence: 99%